Reduced folate carrier 1 gene expression levels are correlated with methotrexate efficacy in Japanese patients with rheumatoid arthritis. Issue 3 (June 2015) - Tazoe, Yui; Hayashi, Hideki; Tsuboi, Seiji; Shioura, Tomone; Matsuyama, Taiji; Yamada, Hiroshi; Hirai, Keita; Tsuji, Daiki; Inoue, Kazuyuki; Sugiyama, Tadashi; Itoh, Kunihiko
Abstract: Responsiveness to methotrexate (MTX), the "anchor drug" for treating rheumatoid arthritis (RA), varies among individual patients. In this study we investigated the effects of folate transporter gene expression levels on disease activity among 56 Japanese patients with RA who were undergoing MTX therapy. We also assessed gene expression levels for 15 healthy control subjects. The mRNA expression levels of reduced folate carrier 1 ( RFC1 ) and proton-coupled folate transporter ( PCFT ) in PBMCs from these patients and controls were determined using real-time quantitative polymerase chain reaction (PCR). Compared with PCFT, there were large individual differences in RFC1 mRNA expression levels in both RA patients and healthy controls. RFC1 mRNA expression levels and RA disease activity scores were significantly negatively correlated, as disease activity scores were lower for patients with higher RFC1 mRNA expression levels. However, RFC1 mRNA levels were not correlated with MTX doses. Thus, the clinical efficacy of MTX for Japanese RA patients was associated with the expression level of a folate transporter gene. Increased RFC1 expression may increase MTX uptake by immune cells, such as lymphocytes, and as a result, RA disease activity would be reduced. Graphical abstract: Increased reduced folate carrier 1 expression may increase methotrexate uptake by immune cells, such as lymphocytes, and as a result, rheumatoid arthritis disease activity would be reduced.